Liposome-Embedding Silicon Microparticle for Oxaliplatin Delivery in Tumor Chemotherapy - Armando Cevenini; Christian Celia; Stefania Orrù; Daniela Sarnataro; Maddalena Raia; Valentina Mollo; Marcello Locatelli; Esther Imperlini; Nicoletta Peluso; Rosa Peltrini; Enrica De Rosa; Alessandro Parodi; et al. (Pharmaceutics, 2020)
Mesoporous silicon microparticles (MSMPs) can incorporate drug-carrying nanoparticles (NPs) into their pores. An NP-loaded MSMP is a multistage vector (MSV) that forms a Matryoshka-like structure that protects the therapeutic cargo from degradation and prevents its dilution in the circulation during delivery to tumor cells. We developed an MSV constituted by 1 µm discoidal MSMPs embedded with PEGylated liposomes containing oxaliplatin (oxa) which is a therapeutic agent for colorectal cancer (CRC). To obtain extra-small liposomes able to fit the 60 nm pores of MSMP, we tested several liposomal formulations, and identified two optimal compositions, with a prevalence of the rigid lipid 1,2-distearoyl-sn-glycero-3-phosphocholine and of 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)-2000]. To improve the MSV assembly, we optimized the liposome-loading inside the MSMP and achieved a five-fold increase of the payload using an innovative lyophilization approach. This procedure also increased the load and limited dimensional changes of the liposomes released from the MSV in vitro. Lastly, we found that the cytotoxic efficacy of oxa-loaded liposomes and-oxa-liposome-MSV in CRC cell culture was similar to that of free oxa. This study increases knowledge about extra-small liposomes and their loading into porous materials and provides useful hints about alternative strategies for designing drug-encapsulating NPs.